Insulin pump therapy in children and adolescents with type 1 diabetes: the italian viewpoint - Pinelli, L.; Rabbone, I.; Salardi, et al., S. (Acta Biomedica Atenei Parmensis, 2008)
Background and Aim: A panel of experts of the Italian Society of Paediatric Endocrinology and Diabetology translated into Italian the international insulin pump therapy recommendations in children and adolescents with type 1 diabetes. Methods: After an extensive review of the literature using evidence-based recommendations, several issues were taken into account, such as patient selection, advantages and disadvantages, instrument choice, insulin type, therapy planning and follow-up, emergencies, nutrition, particular occasions (like parties, holidays, sick days, travels), exercise, continuous glucose monitoring and integrated system, neonatal diabetes. The panel evaluated the cost-effectiveness of insulin pump therapy compared to multiple daily injection therapy, analysing the cost-benefit ratio. Results: Some tweak was needed due to the Italian dietetic singularity, meal schedule, climate and lifestyle. Insulin pump therapy in neonatal diabetes is a new issue and no guidelines have been published yet for this age-group. Moreover, legal issues according to the Italian law have been added and are peculiarity of our recommendations. An “informed therapeutic agreement” between the patient and his/her family and the diabetic team has to be signed before starting insulin pump therapy. Conclusions: We think that nowadays the need for clinical guidelines is important and worth the effort that all countries develop faithful adaptation into their local languages taking into account specific contexts and local peculiarities, without making substantial modifications to the original text.